The Effectiveness of Reality Group Counseling to Improve the Self-Esteem of Students with Low Body Image - Prastika, Berty Surya; Eddy Wibowo, Mungin; Purwanto, Edy (Jurnal Bimbingan Konseling, 2023)
Low body image is potential to cause students have low self-esteem and poor learning concentration. This study aimed to examine the effectiveness of reality group counseling with a classroom meeting and metaphor techniques to improve the self-esteem of students with low body image in Senior High School or SMA grade. During the investigation, the classroom meeting and metaphor techniques were given for four sessions in a framework of a pretest and posttest method analyzed using a Wilcoxon test. In addition, the subjects were the 8 students at SMAN 1 Maospati sampled from 320 total students. Findings showed that the group counseling with a classroom meeting technique was able to improve the self-esteem of the students with low body image. Thus, school counselors are suggested to adopt this treatment to deal with similar issue. Group counseling, classroom meeting, self-esteem, body image,